Applying Systemic Functional Linguistics to Conversations with Dementia: The Linguistic Construction of Relationships between Participants - Müller, Nicole; Mok, Zaneta (Seminars in Speech and Language, 2012)
Social isolation in dementia is a growing concern as the incidence and prevalence of dementing conditions is on the rise in many societies. Positive social interactions, which foster the construction and enactment of positive interpersonal relationships and therefore positive discursive identities, make an important contribution to emotional well-being. In this article, we investigate how two women diagnosed with dementia of the Alzheimer's type use language to relate to each other and two visiting graduate students. We use Systemic Functional Linguistics as an analytical framework, specifically investigating the use of vocatives and naming, and conversational moves and exchanges.
Keywords: dementia; conversation; Systemic Functional Linguistics; interpersonal relationships